2015
DOI: 10.2105/ajph.2015.302610
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Practices of Vapor Store Owners

Abstract: Objectives. We examined the marketing strategies for local vapor stores in a large metropolitan area in Oklahoma. Methods. Vapor store owners or managers (n = 33) participated in individual interviews regarding marketing practices in 2014. We asked owners about their marketing strategies and the groups they targeted. We transcribed the interviews and analyzed them for themes. Results. Store owners used a variety of marketing strategies to bring new customers to their stores and keep current customers coming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 29 publications
(30 reference statements)
1
62
0
Order By: Relevance
“…A recent study based on interviews with vape shop owners has shown that vape shops use marketing practices resembling current and former tobacco industry strategies, and similarly, attempt to target college students and long-term smokers, thus re-establishing a social norm of smoking 25. Youth and young adults are more likely to visit vape shops and experiment with e-cigarettes for the novelty and flavours instead of for smoking cessation.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study based on interviews with vape shop owners has shown that vape shops use marketing practices resembling current and former tobacco industry strategies, and similarly, attempt to target college students and long-term smokers, thus re-establishing a social norm of smoking 25. Youth and young adults are more likely to visit vape shops and experiment with e-cigarettes for the novelty and flavours instead of for smoking cessation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Vape shops not only sell e-cigarettes but also provide a more casual and welcoming environment compared to traditional tobacco retail outlets. Along with traditional marketing, vape shops often encourage their employees to share their personal experience using vaping products 9 25 26. We add to the existing literature by examining vape shop density and proximity along with their associations with college/university characteristics.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9 . Unlike online retailers, vape shops offer a more interactive experience for their customers such as personal interaction with staff members who often also vape, sampling of e-liquids, and customization of vapor devices [9][10][11] . Vape…”
Section: Examining the Smoking And Vaping Behaviors And Preferences Omentioning
confidence: 99%
“…Previous studies show that vape shops play an important role in providing information [24, 25]. Vape shop owners and employees have positive attitudes towards and beliefs about ENDS [2325] and engage in marketing which resembles tobacco industry marketing practices [26]. In addition to selling and providing information about ENDS, vape shops build rapport with customers and create an atmosphere around vaping which allows for interaction, builds a sense of community, and attracts customers [24, 27, 28].…”
Section: Introductionmentioning
confidence: 99%